A simple vibrating sample magnetometer for macroscopic samples - Lopez Dominguez, Virginia Elena (2018)
We here present a simple model of a vibrating sample magnetometer (VSM). The system allows recording magnetization curves at room temperature with a resolution of the order of 0.01 emu and is appropriated for macroscopic samples. The setup can be mounted with different configurations depending on the requirements of the sample to be measured (mass, saturation magnetization, saturation field, etc.). We also include here examples of curves obtained with our setup and comparison curves measured with a standard commercial VSM that confirms the reliability of our device.